Use of covered stents to treat complex cerebrovascular diseases: Expert consensus - Zhu, Yueqi; Tan, Huaqiao; Wu, Zhongxue; Li, Tielin; Ma, Lianting; Liu, Jianmin; Zhang, Hongqi; Gu, Yuxiang; Li, Tianxiao; Guan, Sheng; Xie, Xiaodong; Jiang, Chuhan; et al. (Frontiers in Cardiovascular Medicine, 2022)
The treatment of complicated cerebrovascular diseases (CCVDs) at the skull base, such as complicated intracranial aneurysms, carotid-cavernous sinus fistulas and intracranial artery traumatic injuries, is a difficult clinical problem despite advances in endovascular and surgical therapies. Covered stents or stent graft insertion is a new concept for endovascular treatment that focuses on arterial wall defect reconstruction, differing from endovascular lesion embolism or flow diverter therapies. In recent years, covered stents specially designed for cerebrovascular treatment have been applied in the clinic, allowing thousands of patients with CCVDs to undergo intraluminal reconstruction treatment and achieving positive results, even in the era of flow diverters. Since there is no unified reference standard for the application of covered stents for treating CCVDs, it is necessary to further standardize and guide the clinical application of this technique. Thus, we organized authoritative experts in the field of neurointervention in China to write an expert consensus, which aims to summarize the results of covered stent insertion in the treatment of CCVDs and propose suitable standards for its application in the clinic. Based on the contents of this consensus, clinicians can adopt individualized intraluminal reconstruction treatment techniques for patients with CCVDs.